The Effect of Varenicline on the Neural Processing of Fearful Faces and the Subjective Effects of Alcohol in Heavy Drinkers - Gowin, Joshua L. (Alcohol Clin Exp Res, 2016)
BACKGROUND: Pharmacotherapies for alcohol use disorder have been shown to reduce hazardous drinking and improve overall health. The effect sizes for the effectiveness of these medications, however, are small, underscoring the need to expand the range of therapeutics and develop personalized treatment approaches. Recent studies have suggested that varenicline, an α4β2-nicotinic partial agonist widely used for smoking cessation, can help alcoholics reduce drinking, but the neurocognitive underpinnings of its effectiveness remain largely unexplored. METHODS: In this double-blind study, 32 heavy drinkers were randomized to receive varenicline (2 mg/d) or placebo. After 2 weeks of dosing, participants underwent functional MRI scans, during which they viewed images of faces with either neutral or fearful expressions at baseline and following an intravenous alcohol infusion to a target breath alcohol concentration of 80 mg%. Blood oxygen level-dependent (BOLD) response was analyzed with Analysis of Functional Neuroimaging software. Linear mixed-effects models were used to examine the effects of facial expression (fearful vs. neutral) and medication (placebo vs. varenicline) on BOLD response. The effect of medication on measures of subjective response to alcohol was also examined. RESULTS: Results indicated a significant facial expression-by-medication interaction in the left amygdala. The groups showed equivalent activation to neutral faces, but, whereas the placebo group showed increased activation to fearful faces, the varenicline group showed no change in activation. Amygdala activation to fearful faces correlated with number of drinks in the previous 90 days and Obsessive Compulsive Drinking Scale scores. There was no effect of varenicline on subjective response to alcohol. CONCLUSIONS: Our results indicate that varenicline may disrupt amygdala response to fearful faces in heavy drinkers. Further, amygdala activation correlated with alcohol consumption, suggesting that the effects of varenicline may be related to aspects of drinking behavior. These results suggest that amygdala response to fearful faces may be developed as a biomarker of the effectiveness of medications being developed for the treatment of alcohol use disorder.